Composite membranes of polyacrylonitrile cross-linked with cellulose nanocrystals for emulsion separation and regeneration. (January 2023) - Wang, Dong; Yang, Haiying; Wang, Qingxiang; Lu, Yi; Yan, Jie; Cheng, Wanli; Rojas, Orlando J.; Han, Guangping
Graphical abstract: Highlights: Composite nanofiber membranes were synthesized by crosslinking PAN and CNC. PAN hydrolysis contributes to the durability of the membrane. H-bonding networks enable membrane operation stability in aqueous media. The membrane can be reused and shows excellent emulsion separation performance. Abstract: As a result of fatigue and damage, the durability of separation membranes remains a major challenge for long-term use in the separation of multiphase systems, such as oily water and emulsions. Here, we synthesize electrospun membranes based on hydrolyzed polyacrylonitrile reinforced with cellulose nanocrystals (CNC). The nanofibers form highly porous systems that are held together by crosslinking, allowing fast mass transport while achieving high tensile strength and elongation at break. The membranes exhibit shape retention upon immersion in complex fluids. An underwater oil contact angle of 141° enables efficient emulsion separation (98.2 % separation at a flux as high as 1293 L·m −2 ·h −1 for hexane-in-water emulsions) and reliable operation for at least 20 filtration cycles. A similar performance is achieved in the separation of emulsions based on toluene, petroleum ether, diesel, and vegetable oils. Overall, the designed composite membranes endow stable three-dimensional structures, excellent durability, and separation performance.